Biosynthesis of zinc oxide nanoparticles using leaf extracts of Alchornea laxiflora and its tyrosinase inhibition and catalytic studies. (February 2021) - Ekennia, Anthony; Uduagwu, Dickson; Olowu, Olawale; Nwanji, Obianuju; Oje, Obinna; Daniel, Blessing; Mgbii, Sandra; Emma-Uba, Chimerem
Highlights: Biosynthesis of quasi-hexagonal shaped zinc oxide nanoparticles. Photocatalytic degradation of Congo red dye solution using as-synthesized ZnO-NPs. Tyrosinase inhibition activity of the ZnO-NPs using Mushroom tyrosine enzyme. Enzyme kinetics and the mechanism of inhibition using Line-weaver – Burk model. Abstract: Zinc oxide nanoparticles (ZnO-NPs) were synthesized using a simple, low cost and safe method involving aqueous leaf extracts of Alchornea laxiflora and a zinc precursor salt. The nanoparticles were characterized by ultraviolet-visible (UV–vis), Fourier transform (FT-IR) spectroscopy, Energy dispersive X-ray (EDX), X-ray diffraction (XRD) and Scanning electron microscope (SEM). They were evaluated for their potentials as tyrosinase inhibitors and as catalysts in the degradation of Congo red dye. The UV–vis spectra gave characteristic surface Plasmon bands within the range 276−456 nm. The band gap energies of the ZnO-NPs were of the range, 2.50–3.67 ev. The SEM results showed average sizes of 29 nm and 38 nm for particles obtained using 1 mL and 2 mL of the plant extracts respectively. EDX plot showed the elemental compositions of the nanoparticles with zinc and oxygen being pronounced. The ZnO nanoparticles exhibited good photocatalytic efficiency of 87 % degradation of Congo red (CR) dye molecules in 60 min, They also showed good anti-tyrosinase ability with an IC50 of 66.28 μg/mL. Overall the biogenic ZnO nanoparticles are promising materials for dual applications as photocatalysts in the degradation of Congo red dye and as tyrosinase inhibitors.